Efficiency Of Bed Utilization By Class Type Using Barber Johnson Chart In RSU Imelda Pekerja Indonesia Medan In 2023 - Mei Sryendang Sitorus; Nila Sari; Anna Nadiyas Kristiani Lase (Jurnal EduHealth, 2023)
One indicator of service quality in hospitals is the efficiency of inpatient services, especially in the use of beds. The efficiency of bed utilization can be seen from the Barber Johnson chart based on the calculation of Bed Occupancy Rate (BOR), Length Of Stay (LOS), Turn Over Interval (TOI) and Bed Turn Over (BTO). The initial survey conducted, medical record officers of RSU Imelda Pekerja Indonesia Medan have never analyzed the efficiency of bed utilization based on class type using the Barber Johnson chart. The purpose of this study was to determine the efficiency of bed utilization based on class type using the Barber Johnson chart. This type of research is Mix Methods. Primary data in this study are the results of researcher observations and secondary data data obtained from the medical records work unit and SIRS RSU Imelda Pekerja Indonesia Medan. Data collection in this study was carried out using interview and observation techniques. The results of the study were that the BOR value did not meet the Barber Johnson standard, namely class I inpatient rooms (48%), class II (38%) and class III (60%). The LOS value has met the Barber Johnson ideal value standard, namely class I inpatient rooms (4.2 days), class II (4.5 days) and class III (4.2 days). The TOI value still exceeds the Barber Johnson standard value, namely class I inpatient rooms (7.7 days), class II (8.7 days), class III (3.3 days). The BTO value in class I (28 times) and class II (25.5 times) inpatient rooms is still not in accordance with the Barber Johnson standard, while class III (43.5 times) is in accordance with the Barber Johnson ideal value standard. the meeting point on the Barber Johnson graph of class I, class II and class III inpatient rooms is still outside the efficient area so that the indicators of the RSU Imelda Pekerja Indonesia inpatient room are still not efficient.